Another Form of Neighborhood Effect Bias:The Neighborhood Effect Polarization Problem (NEPP). (7th February 2023) - Wu, Jiayu; Wang, Binhui; Ta, Na; Chai, Yanwei
Abstract : The neighborhood effect averaging problem (NEAP) points out that the effect and statistical significance of mobility-dependent environmental exposure on health behaviors or outcomes by the residence-based approach might be overestimated compared with the exposure estimates considering daily mobility. NEAP studies, however, are recently only proven in pollution and congestion exposure. The neighborhood effect bias might have another form in other environmental exposures, the neighborhood effect polarization problem (NEPP), which describes the situation where the overall trend of mobile exposure is more polarized than residential exposure. Taking green exposure as a typical case, 554 Beijing residents were studied regarding the relationship between residence- and mobility-based green exposures. After controlling socioeconomic factors, time, and other built environmental factors, the cluster robust logit and ordinary least squares models combined with the parameter test were used to discuss the neighborhood effect trend of green exposure under the background of mobility. The results show the following: (1) NEPP exists in green exposure; (2) NEPP is most likely to occur when residential green space is measured by accessibility and visibility; and (3) the green demand of residential green advantaged groups is higher, which is the potential cause of NEPP. This study demonstrates the existence of NEPP and reveals another form of neighborhood health effect bias and potentially more serious environmental justice problems that exist in the travel environment.